The socioimaginary construction of women in the Chilean’s press discourse: the case of "El Diario Austral" of Temuco in the context of the promulgation of the right to vote for women in Chile 1935-1952 - López Dietz, Sandra; Mayorga Rojel, Alberto Javier; Nitrihual Valdebenito, Luis (Estudios sobre el Mensaje Periodístico, 2018)
The aim of this work is to present the results of one research about the social imaginary surrounding the woman in the press’s discourse of El Diario Austral of Temuco, during the period 1935-1952, years in which the women’s suffrage was promulgated for the municipal elections, and then, was widened for presidential and parliamentary elections.
Keywords: Press; social imaginaries; woman; discourse analysis.